Habituation or sensitization of brain response to food cues: Temporal dynamic analysis in an functional magnetic resonance imaging study - Ghobadi-Azbari, Peyman; Mahdavifar Khayati, Rasoul; Ekhtiari, Hamed (Frontiers in Human Neuroscience, 2023)
In the modern obesogenic environment, heightened reactivity to food-associated cues plays a major role in overconsumption by evoking appetitive responses. Accordingly, fMRI studies have implicated regions of the salience and reward processing in this dysfunctional food cue-reactivity, but the temporal dynamics of brain activation (sensitization or habituation over time) remain poorly understood. Forty-nine obese or overweight adults were scanned in a single fMRI session to examine brain activation during the performance of a food cue-reactivity task. A general linear model was used to validate the activation pattern of food cue reactivity in food > neutral contrast. The linear-mixed effect models were used to examine the effect of time on the neuronal response during the paradigm of food cue reactivity. A linear mixed-effect model revealed a trend for the time-by-condition interactions in the left medial amygdala (t(289) = 2.21, β = 0.1, P = 0.028), right lateral amygdala (t(289) = 2.01, β = 0.26, P = 0.045), right nucleus accumbens (t(289) = 2.81, β = 0.13, P = 0.005) and left dorsolateral prefrontal cortex (t(289) = 2.58, β = 0.14, P = 0.01), as well as in the left superior temporal cortex (42 Area: t(289) = 2.53, β = 0.15, P = 0.012; TE1.0_TE1.2 Area: t(289) = 3.13, β = 0.27, P = 0.002). Habituation of blood-oxygenation-level-dependent (BOLD) signal during exposure to food vs. neutral stimuli was evident in these regions. We have not found any area in the brain with significant increased response to food cues over time (sensitization). Our results elucidate the temporal dynamics of cue-reactivity in overweight and obese individuals with food-induced craving. Both subcortical areas involved in reward processing and cortical areas involved in inhibitory processing are getting habituated over time in response to food vs. neutral cues. There were significant bivariate correlations between self-report behavioral/psychological measures with individual habituation slopes for the regions with dynamic activity, but no robust cross-unit latent factors were identified between the behavioral, demographic, and self-report psychological groups. This work provides novel insights into dynamic neural circuit mechanisms supporting food cue reactivity, thereby suggesting pathways in biomarker development and cue-desensitization interventions.